Chronic wasting disease risk assessment in Portugal: analysis of variability and genetic structure of the portuguese roe deer populatio - Gonçalves-Anjo, Nuno (2022)
Among the Transmissible Spongiform Encephalopathies, Chronic Wasting Disease (CWD) in cervids is now the rising concern in wildlife within Europe after the first case detected in Norway in 2016. CWD shows a notable horizontal transmission, affecting both free-ranging and captive cervids. Furthermore, several genetic variants in the Prion Protein (PRNP) gene coding sequence of the cervid were identified, which increase the susceptibility to the disease. Roe deer has a widespread geographical distribution which extends from the Iberian Peninsula to the north of Scandinavia, being found as well in Turkey, Israel, and Jordan. In recent centuries, a significant number of fluctuations have occurred in these deer populations, leading to a decline in deer population and distribution. These alterations combined with translocations of animals of the same species, can drive to meaningful consequences on the genetic structure, diversity, and fitness of populations.